Blood trail - Box, C. J. (New York : Berkley Prime Crime, 2009)
In the wake of an elk hunter's grisly murder, Wyoming game warden Joe Pickett is directed by the governor to investigate the relevance of a mysterious poker chip found at the crime scene.
Originally published: New York : G.P. Putnam's Sons, 2008.
"A Joe Pickett novel"--Cover.
"Berkley Prime Crime mystery"--Spine.
Keywords: Pickett, Joe (Fictitious character); Game wardens; Hunters -- Crimes against; Game protection; Wyoming; Fiction; Mystery fiction